The Role of Color Grading in Enhancing Aesthetic Quality and Strengthening Visual Narrative in Documentary Films - Gita Riyanti Fadhilah (Universitas Muhammadiyah Palu, 2025)
This study explores the role of color grading in enhancing aesthetic quality and strengthening visual narratives in documentary films. As a post-production process, color grading is not limited to technical correction but functions as an artistic strategy that influences tone, atmosphere, and coherence. The research adopts a qualitative descriptive approach using content and semiotic analysis of selected documentary films released between 2018 and 2024, recognized internationally for their innovative use of grading. The findings are supported by triangulation of visual frame analysis, practitioner interviews, and secondary literature, ensuring credibility and depth of interpretation.The results indicate that color grading significantly enhances the aesthetic dimension of documentaries by creating consistent visual harmony and elevating cinematic appeal. It also strengthens narrative coherence by unifying diverse visual sources, distinguishing temporal and spatial contexts, and embedding symbolic meaning within the storyline. Furthermore, grading was found to be central to audience emotional engagement, shaping affective responses such as empathy, nostalgia, and tension. The study also highlights the cultural dimension of color, emphasizing how interpretations vary across audiences and necessitate culturally sensitive grading strategies for global distribution. Finally, technological innovations such as HDR workflows, LUTs, and AI-assisted grading were identified as transformative tools that expand creative possibilities, ensure consistency across platforms, and support sustainable production practices.In conclusion, color grading emerges not only as a technical process but also as an essential narrative and cultural instrument. Its dual function—enhancing visual beauty and directing audience perception—positions color grading as a core element in shaping impactful documentary storytelling in the digital era.